2022
DOI: 10.1155/2022/4958089
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Risk Factors of Persistent Pain following Total Knee Arthroplasty

Abstract: Background. Despite good results of total knee arthroplasty (TKA) as a treatment of idiopathic osteoarthritis (OA) of the knee, significant number of patients (16-33%) complain of persistent pain of unknown origin. This phenomenon is the major cause of patient’s dissatisfaction. It has been theorized that certain preoperative factors may increase the risk of persistent pain; hence, their identification should enable proper preoperative education and development of realistic expectations regarding results of TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Sample sizes ranged from 26 [43] to 5309 [50]. We excluded eight studies from analysis because attempts to obtain missing data from authors were unsuccessful or insufficient [62][63][64][65][66][67][68][69]. The search strategy, subject headings and keywords customized for all databases is presented in S8 Appendix and reasons for study exclusion are in S9 Appendix.…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged from 26 [43] to 5309 [50]. We excluded eight studies from analysis because attempts to obtain missing data from authors were unsuccessful or insufficient [62][63][64][65][66][67][68][69]. The search strategy, subject headings and keywords customized for all databases is presented in S8 Appendix and reasons for study exclusion are in S9 Appendix.…”
Section: Resultsmentioning
confidence: 99%
“…The present study found that preoperative VAS scores influenced the achievement of beneficial outcomes. In fact, preoperative knee pain was identified as a significant contributor to poor outcomes after TKA and increased the risk of postoperative dissatisfaction by 2.49-fold 9 , 40 . The VAS for pain is a common method for evaluating arthritis pain and is a highly sensitive metric 41 .…”
Section: Discussionmentioning
confidence: 99%
“…For opioid use, higher presurgical opioid consumption has been associated with use of higher oral morphine equivalents (OME) more than 6 months after surgery compared with patients with no or low opioid use before surgery [10]. Duration of pain before undergoing surgery has also been shown to be a risk factor [4] as well as the combination of high preoperative pain and low radiographic evidence of osteoarthritis [11].…”
Section: Risk Factors For Chronic Pain After Total Knee Arthroplastymentioning
confidence: 99%
“…For opioid use, higher presurgical opioid consumption has been associated with use of higher oral morphine equivalents (OME) more than 6 months after surgery compared with patients with no or low opioid use before surgery [10]. Duration of pain before undergoing surgery has also been shown to be a risk factor [4] as well as the combination of high preoperative pain and low radiographic evidence of osteoarthritis [11]. There is some evidence that psychological risk factors also play a role in CPSP after TKA, with evidence that persons with central sensitization of pain and higher levels of pain catastrophizing have higher risk of persistent pain [12,13].…”
Section: Risk Factors For Chronic Pain After Total Knee Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation